2012
DOI: 10.1002/maco.201206584
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of electrochemical methods for the removal of chloride ions from iron marine archaeological objects: A comparative study

Abstract: The conservation of archaeological marine iron artefacts requires chloride ions removal. In this study, the removal of chloride ions was undertaken by two electrochemical methods: the electrolytic and the galvanic reduction in alkaline media. The results were compared with those obtained by the washing and the sulphite reduction methods, under identical conditions. The experiments were performed on samples coming from an 18th century cast iron cannon‐ball, found in the archaeological context of a shipwreck, l'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…[7][8][9][10] To mitigate this,several desalination treatments have been proposed that aim to remove as much Cl as possible from the artefact. [15] Comparison of different conservation methods [10,[16][17][18] has been limited by the variability of both objects and burial environments.Asaresult, it is often not possible to attribute differences in treatment success to technique used, while studying material that accurately reflects an archaeological artefact. [15] Comparison of different conservation methods [10,[16][17][18] has been limited by the variability of both objects and burial environments.Asaresult, it is often not possible to attribute differences in treatment success to technique used, while studying material that accurately reflects an archaeological artefact.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] To mitigate this,several desalination treatments have been proposed that aim to remove as much Cl as possible from the artefact. [15] Comparison of different conservation methods [10,[16][17][18] has been limited by the variability of both objects and burial environments.Asaresult, it is often not possible to attribute differences in treatment success to technique used, while studying material that accurately reflects an archaeological artefact. [15] Comparison of different conservation methods [10,[16][17][18] has been limited by the variability of both objects and burial environments.Asaresult, it is often not possible to attribute differences in treatment success to technique used, while studying material that accurately reflects an archaeological artefact.…”
mentioning
confidence: 99%
“…These techniques can be divided into two categories:r eductionbased, [11][12][13] where Cl À is removed by transformation of chorine-containing Fe III crystals,a nd washing methods [10,14] that remove chlorine by diffusion into aqueous solution. [15] Comparison of different conservation methods [10,[16][17][18] has been limited by the variability of both objects and burial environments.Asaresult, it is often not possible to attribute differences in treatment success to technique used, while studying material that accurately reflects an archaeological artefact. To overcome these issues,t his work focuses on the collection of 1248 cast iron cannon shot from the Mary Rose.…”
mentioning
confidence: 99%
“…The cannonballs from the Spanish wrecks, in accordance with their microstructures and chemical composition (3.1 < C > 2, 0.3 < Si > 1.8, 0.37 < Mn > 1, 0.01 < S > 0.1, 0.074 < P > 0.27), were identified as having been produced by blast furnaces in Spain. On the other hand, Coelho et al () have reported the metallurgical characteristics of an 18th‐century iron cannonball coming from the l'Ocean shipwreck, found near the southern Portuguese coast, which has micro‐constituents similar to those obtained from the cannonball from the Fortress of San Juan de Ulúa; however, the carbon (6–7 wt%) and silicon (0.5–0.6 wt%) contents are much higher than the values reported in Table .…”
Section: Resultsmentioning
confidence: 92%
“…The exterior shank of bolt 1 had a concentration of 0.24 wt% carbon, probably due to the heavy corrosion attack of the outer surfaces containing high carbon concentrations. Such carbon degradation is common among iron objects excavated from marine environments (Coelho et al 2014). The heterogeneous microstructure, with a higher concentration of carbon on the external surface, indicated carburization.…”
Section: The Boltsmentioning
confidence: 99%